VizieR Online Data Catalog: MS bands of SiC2 in LMC carbon stars (Morgan+, - Morgan, D. H.; Hatzidimitriou, D.; Cannon, R. D. (2005)
From a sample of 304 carbon stars in the central parts of the Large Magellanic Cloud (LMC), ~27 per cent have Merrill-Sanford (MS) bands of the SiC2 molecule. The data are based on a uniform set of spectra taken with 2dF on the Anglo-Australian Telescope, and give useful statistics on the incidence of MS bands and on their correlation (or otherwise) with other properties. All of these are red stars, cooler than 3100 K. The proportion of stars showing the bands is highest amongst the coolest stars, but not all very cool stars show the bands. There is no evidence that MS bands are more common in J-type stars (carbon stars with a high 13C/12C ratio) than in N-type carbon stars, at least within this sample of LMC stars. There is no apparent correlation with stellar variability, or between the photospheric temperature [as measured by (J-K)] and the occurrence of the 'hot' MS bands from excited molecular states. (2 data files).
Keywords: Magellanic Clouds; Spectroscopy; Stars: carbon